Experimental Study on Seepage Characteristics of Coal Containing Gas and Water - Shuyin Ma; Qinghua Zhang; Sheng Xue (Geofluids)
The effect of gas drainage is often affected by water after hydraulic infiltration enhancement measures are adopted for soft and weak permeability coal. In order to understand the permeability characteristics of coal in the state of gas and water, a three-phase pipe domain model is established. Using the improved triaxial seepage test platform, three groups of cyclic seepage tests under different pressure and water injection conditions are carried out on three groups of raw coal samples under the conditions of constant temperature, fixed axial pressure, and confining pressure. The test results show that (1) after the test of three groups of circulating coal samples, the moisture content of each group of coal samples is different. The change trend of permeability of the first cycle natural coal sample and the second cycle pressureless water injection coal sample is similar to that of gas pressure, which decreases slowly with the increase of gas pressure and the permeability of the third cycle pressure water injection coal sample increases with the increase of gas pressure, which is different from the first two cycles. (2) In the ultrasonic wave velocity test of pressure water injection, the change trend of longitudinal wave velocity of coal sample is opposite to that of gas pressure, that is, the longitudinal wave velocity decreases with the increase of gas pressure. When the gas pressure is 0.9 MPa to 1.0 MPa, the reduction of longitudinal wave velocity is more significant. (3) During the test, when the gas pressure of the coal sample is less than 1.11 MPa, the gas sensitivity coefficient of the third cycle pressurized water injection coal sample is lower than that of the first two cycles. When the gas pressure increases to 1.11 MPa, there is an inflection point; that is, the gas sensitivity coefficient of the third cycle pressurized water injection coal sample is higher than that of the first two cycles.